Schooling costs and child labour in rural Pakistan - Gautam Hazarika; Arjun S. Bedi (University of Bonn, Center for Development Research (ZEF), 2002)
A conventional argument in the child-labor debate is that improvements in access to schools are an effective way to reduce the labor force participation of children. It is argued that schooling competes with economic activity in the use of children's time, and enhanced access to schools, interpretable as reduction in schooling costs, may raise school attendance at the expense of child labor. In this paper, we draw a distinction between child labor within the household (intra-household) and child work in the labor market (extra-household), and examine the separate effects of schooling costs on the two types of child labor. Consistent, at least in part, with our theoretical framework, we find that extra-household child labor and schooling costs are positively related while intra-household child labor is insensitive to changes in the costs of schooling. Our results suggest that reduction in schooling costs will have limited success in the abatement of child labor in rural Pakistan.
Keywords: 330; Labor and Human Capital; Kinderarbeit; Schüler; Bildungsverhalten; Bildungsfinanzierung; Haushaltsökonomik; Arbeitsangebot; Schätzung; Ländlicher Raum; Pakistan